2020
DOI: 10.1002/cbin.11409
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of fibroblast growth factor‐21 (FGF‐21) protects mesenchymal stem cells against caspase‐dependent apoptosis induced by oxidative stress and inflammation

Abstract: The clinical application of stem cells offers great promise as a potential avenue for therapeutic use in neurodegenerative diseases. However, cell loss after transplantation remains a major challenge, which currently plagues the field. On the basis of our previous findings that fibroblast growth factor 21 (FGF‐21) protected neurons from glutamate excitotoxicity and that upregulation of FGF‐21 in a rat model of ischemic stroke was associated with neuroprotection, we proposed that overexpression of FGF‐21 protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 27 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…Ghazavi et al investigated the effect of AD-MSCs transfected with FGF1 and found that compared with normal AD-MSCs, the former could increase the level of FGF1 in the ischemic lesions, reduce apoptotic cells, and infarct size more significantly [61]. In addition, Linares et al found that FGF21 transfected MSCs have strong antiapoptotic ability in vitro in the face of oxidative stress and inflammatory environment, which suggests that FGF21 transfected MSCs may have stronger survival ability and neuroprotective ability in infarcted lesions [168]. LV et al found that transplanted MSCs overexpressing HIF-1α had increased viability in ischemic lesions and showed a more significant reduction of infarct size and recovery of neurobehavior, which was related to the further decrease of proinflammatory cytokines and increase of neurotrophic factors [169].…”
Section: Gene Transfection or Overexpressionmentioning
confidence: 99%
“…Ghazavi et al investigated the effect of AD-MSCs transfected with FGF1 and found that compared with normal AD-MSCs, the former could increase the level of FGF1 in the ischemic lesions, reduce apoptotic cells, and infarct size more significantly [61]. In addition, Linares et al found that FGF21 transfected MSCs have strong antiapoptotic ability in vitro in the face of oxidative stress and inflammatory environment, which suggests that FGF21 transfected MSCs may have stronger survival ability and neuroprotective ability in infarcted lesions [168]. LV et al found that transplanted MSCs overexpressing HIF-1α had increased viability in ischemic lesions and showed a more significant reduction of infarct size and recovery of neurobehavior, which was related to the further decrease of proinflammatory cytokines and increase of neurotrophic factors [169].…”
Section: Gene Transfection or Overexpressionmentioning
confidence: 99%
“…To date, evidence suggests that OS stimulates FGF21 production, 8,12,13 and other studies have demonstrated that FGF21 protects cells from OS injury and death in cardiac cells exposed to hydrogen peroxide; 42 neuroblastoma cells (SH-SY5Y) exposed to amyloid-beta 1-42 ; 43 mesenchymal stem cells exposed to hydrogen peroxide and tumor necrosis factor alpha (TNFa); 44 and in vivo in a rodent model of sciatic crush injury, 45 FGF21 has shown an antioxidant and protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…MSCs possess self-renewal capacities and are able to differentiate into many specialized cell types including neurons (Tropel et al, 2006 ). Recently, several preclinical animal and clinical studies have investigated the applications of MSCs for the treatment of epilepsy and appear potentials to ameliorate the severity of epilepsy and attenuate epilepsy-induced excitotoxicity, oxidative stress, and neuroinflammation (Fukumura et al, 2018 ; Milczarek et al, 2018 ; Papazian et al, 2018 ; Kodali et al, 2019 ; Xian et al, 2019 ; Linares et al, 2020 ). Furthermore, stem cell therapy using MSCs allows either allogeneic or autologous transplantation that extends the clinical feasibility.…”
Section: Sources and Types Of Stem Cellsmentioning
confidence: 99%